The North Pole Mission in Iceland 1857 - 1858 - Birgir Guðmundsson 1956-; Meckl, Markus, 1967- (2014)
In 1857 two catholic priests came to Iceland in order to regain the island for the catholic faith. The recently open polar mission within in the catholic church had the ambition aim to missionaries Northern Scandinavia, the Faroe and Shetland Islands as well as Iceland, Greenland and artic regions of Northern America. Behind this mission was a former Russian aristocrat Stepan Stephanovic Dzunkovskij who had converted to the Catholic Church and got the support by the Vatican to run this operation. At the archive at the Catholic Church in Iceland in Reykjavik are six boxes containing the correspondence between the priest coming to Iceland and the mission as well many other documents concerning this first 30 years of the Catholic Church in Iceland. Up to 80 percent of these documents are in French, less than 5 percent are in Icelandic. The main object of the presentation is to make accessible the content of the archive and by doing so help to better understand the beginning of the Catholic Church in Iceland. It will be also a contribution to the social history of Iceland at the middle of the 19th century and will allow seeing Iceland through the eye of a 19th century foreigner.